The Foot From Evaluation to Surgical Correction - Klaue, Kaj.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
This superbly illustrated book guides the reader on a rational pathway from anamnesis and clinical examination through radiological screening to the appropriate surgical solution for a wide range of foot conditions. Proposed treatments and follow-up results are presented in detail with the aid of intra- and postoperative photographs and radiographs. A key feature is the focus on systematic description, and the treatment-related chapters include numerous references to earlier parts of the book in order to clearly link the preoperative evaluation to the treatment. It is particular to the surgical correction of foot and ankle pathology that the treatment is nearly always "composite" or complex, in that it entails several separate actions. Thus, surgical correction often has one or more structural components (e.g., osteotomy, arthrodesis) and one or more functional or motor components. The book aims to explain the rationale and effect of every one of these components. The new edition includes updated guidance on clinical examination, a series of cases demonstrating the composite approach to complex reconstructions, and detailed coverage of the treatment of diabetic arthropathyabetic arthropathy.
Introduction -- Clinical Examination -- Radiologic Screening -- Surgical Orthopedic Treatment -- Surgical Fracture Treatment -- Operative Techniques -- Complex surgical orthopaedic treatment -- References.
Keywords: Orthopedics; Surgery; Radiology; Orthopaedics; Surgery; Radiology; Foot Diseases -- diagnosis; Foot Diseases -- surgery; Foot -- surgery